Solid dispersion of quercetin-PVP K-30 and its effects on the antioxidant activity - Zahara Gayo; Henny Lucida; Erizal Zaini (Jurnal Ilmiah Farmasi, 2020)
AbstractBackground: Quercetin (3,3’,4’,5,7-pentahydroxil-flavon) is a flavone and secondary metabolite known as flavonoid. Quercetin belongs to class II BCS that has low solubility and high permeability. The poor solubility of quercetin restricts the accessibility and bioavailability.Objectives: To increase the solubility, dissolution, and antioxidant activity in a solid dispersion system.Methods: Preparation of quersetin-PVP K-30 solid dispersion was conducted using the freeze-drying method at -96 degree C for 24 hours with a ratio of 1:1, 1:0.5, and 0.5:1 and a 1:1 physical mixture of quercetin-PVP K-30. The solid dispersion of quercetin-PVP K-30 was characterized by Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD) analysis, and FT-IR spectrophotometric analysis. Solubility test was analyzed using a UV-Vis spectrophotometer, dissolution test was done using a paddle-type dissolution tester, dissolved quercetin concentrations were analyzed using a UV-Vis spectrophotometer, and antioxidant activity was determined using the DPPH method in a UV-Vis spectrophotometer.Results: SEM analysis showed the formation of quercetin-PVP K-30 solid dispersion using the freeze-drying method, and the form changed into anhydrate as seen from the XRD results with the presence of new crystalline peaks in solid dispersion, which were not seen in pure quercetin and PVP K-30. Quercetin-PVP K-30 solid dispersion could increase the solubility by 54-fold at a ratio of 0.5:1 with 94.36%±0.85 quercetin dissolved in 120 minutes. The formation of this solid dispersion affected the antioxidant activity which was observable from the IC50 value at the best ratio of 0.5:1 reaching 0.714 microgram/mL while the IC50 value of pure quercetin is 1.102 microgram/mL.Conclusion: The formation of quercetin solid dispersion could increase the solubility and dissolution and affect the antioxidant activity.Keywords: solid dispersion, freeze-drying, quercetin, antioxidantIntisariLatar Belakang: Kuersetin (3,3’,4’,5,7-pentahydroxil flavon) adalah flavon dan merupakan metabolit sekunder yang dikenal dengan flavonoid. Kuersetin tergolong dalam BCS kelas II yaitu memiliki kelarutan rendah dan permeabilitas tinggi (low solubility and high permeability drugs), kelarutan kuersetin yang buruk membatasi aksesibilitas dan bioavailabilitasnya.Tujuan: Untuk meningkatkan kelarutan dan disolusi kuersetin serta melihat pengaruhnya terhadap aktivitas antioksidan kuersetin.Metode: Pembuatan dispersi padat menggunakan metode freeze dry pada suhu -96 derajat C selama 24 jam.Hasil: Dengan pembuatan disepersi padat kuersetin-PVP K-30 dapat meningkatkan kelarutan, disolusi dan dapat meningkatkan aktivitas antioksidan kuersetin.Kesimpulan: Uji statistik menggunakan ANOVA dua arah menunjukkan uji kelarutan dan disolusi pada pembentukan dispersi padat kuersetin-PVP K-30 terdapat perbedaan yang signifikan (p= 0,000 (Sig<0,05)).Kata Kunci: Dispersi padat, Freeze Dry, Kuersetin, Antioksidan